An Annual Index of U. S. Industrial Production, 1790-1915 - Davis, J. H. (Quarterly Journal of Economics, 2004)
As a remedy for the notorious deficiency of pre-Civil War U. S. macroeconomic data, this study introduces an annual index of American industrial production consistently defined from 1790 until World War I. The index incorporates 43 quantity-based annual series (most entirely new) in the manufacturing and mining industries in a manner similar to the Federal Reserve Board's monthly industrial production index. The index changes our view of the growth and volatility of the U. S. economy before World War I. A direct implication of the index is that antebellum-postbellum differences in industrial volatility are statistically indistinguishable. The index also demonstrates that the pernicious deflationary depressions that purportedly followed the financial panics in 1837 and 1873 were actually rather mild recessions when expressed in real output.